2020
DOI: 10.1161/circulationaha.119.042336
|View full text |Cite
|
Sign up to set email alerts
|

SNO-MLP (S-Nitrosylation of Muscle LIM Protein) Facilitates Myocardial Hypertrophy Through TLR3 (Toll-Like Receptor 3)–Mediated RIP3 (Receptor-Interacting Protein Kinase 3) and NLRP3 (NOD-Like Receptor Pyrin Domain Containing 3) Inflammasome Activation

Abstract: Background: S-nitrosylation (SNO), a prototypic redox-based posttranslational modification, is involved in the pathogenesis of cardiovascular disease. The aim of this study was to determine the role of SNO of MLP (muscle LIM protein) in myocardial hypertrophy, as well as the mechanism by which SNO-MLP modulates hypertrophic growth in response to pressure overload. Methods: Myocardial samples from patients and animal models exhibiting myocardial hypertro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 50 publications
2
39
0
Order By: Relevance
“…Especially during inflammation, ROS levels can acutely increase and result in oxidative modification of proteins 6 . Cysteine (Cys) is an amino acid that is susceptible to several types of oxidative posttranslational modification including sulfenylation, disulfide formation, S-glutathionylation, and S-nitrosylation 9,40 . Oxidative modifications of proteins are critical mediators of compartmentalized ROS signaling 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Especially during inflammation, ROS levels can acutely increase and result in oxidative modification of proteins 6 . Cysteine (Cys) is an amino acid that is susceptible to several types of oxidative posttranslational modification including sulfenylation, disulfide formation, S-glutathionylation, and S-nitrosylation 9,40 . Oxidative modifications of proteins are critical mediators of compartmentalized ROS signaling 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TET2 deficiency enhanced IL‐1β expression, whereas MCC950 treatment significantly decreased HF development 53 . Recently, increased S‐nitrosylation of muscle LIM protein (MLP) in pressure‐overloaded HF was reported to induce the formation of a complex between Toll‐like receptor 3 (TLR3) and receptor‐interacting protein kinase 3 (RIP3), thereby activating NLRP3 inflammasome and promoting the progression of myocardial hypertrophy 54 . However, some studies have reported contradictory findings.…”
Section: Nlrp3 Inflammasome In the Pathogenesis Of Cvdsmentioning
confidence: 99%
“…RIP3 plays a role in the convergence points of multiple necrotic cell death pathways. 24,[48][49][50][51][52][53][54] Normally, the activation of death receptors can trigger programmed necrosis, but it can also be activated through non-death receptor-dependent pathways. In the death receptor-dependent pathway, the receptor is recruited through the death domain to form complex I after ligand binding.…”
Section: Discussionmentioning
confidence: 99%